Rural poverty and labour force participation: Evidence from Indonesia’s Village fund program - Anu Rammohan; Achmad Tohari (PLoS ONE, 2023)
Rural residents account for the bulk of poverty in developing countries. This paper evaluates the impact of Indonesia’s Dana Desa program (Village Fund Program or VFP) on rural poverty and female labour force participation. The VFP, introduced in 2014, was an ambitious national-level village governance program which transferred administrative responsibility and financial resources to Indonesia’s 79,000 plus rural villages, providing them with the autonomy to invest in rural infrastructure, human capital, and job creation programs. Using nationally representative data from before and after the program, we show that the implementation of the VFP was associated with an improvement in rural household’s consumption expenditure among households, particularly among agricultural households. Female labour force participation in rural areas increased by about 10 percentage points and there is also evidence of a sectoral shift away from agricultural employment towards jobs in the service sector. This improvement in labour force participation is associated with poverty reduction among rural households.